Relativity - Hayes, Antonia (Gallery Books, 2016)
"In the vein of Jodi Picoult's House Rules and Nick Hornby's About a Boy, a debut novel about an exceptionally gifted boy who discovers the truth about his past, his overprotective single mother who tries desperately to shield him from it, and the father he has never met who is trying to come back into his life"--